80‐3: Research on ZnO‐MgO QDs and its Application in QLED. Issue 1 (30th May 2018) - Li, Qing; Sun, Yi; Zhang, Xu; Zhang, Zhenbo; Khan, Qasim; Chen, Jing; Lei, Wei; Xia, Jun
Abstract : Colloidal ZnO‐MgO core‐shell QDs are synthesized. The UV light is attributed to prominent near‐band‐edge emission, whereas visible light is caused by defect states emission, which is suppressed at an optimized anneal temperature for QD films. A QLED with structure ITO/PEDOT:PSS/PVK/QDs/Al is fabricated, resulting in electroluminescence of UV light centered at 370 nm.